Positive electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
Patent Information
- Application Number
- CN202180035066.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-29
- Filing Date
- 2021-04-20
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-04-20
AI Technical Summary
[0009]根据本公开的一方式的非水电解质二次电池用正极活性物质,可以减小二次电池的电阻,且抑制伴有充放电的电池容量的降低。
Smart Images

Figure CN115606016B_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to a positive electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery. Background Technology
[0002] Lithium transition metal composite oxides have long been widely used as positive electrode active materials for secondary batteries such as lithium-ion batteries. For high-capacity secondary batteries, lithium-excess positive electrode active materials containing a large amount of lithium have attracted considerable attention. Furthermore, secondary batteries are required to maintain their capacity even after repeated charge-discharge cycles. For example, Patent Document 1 discloses a lithium-ion secondary battery that improves charge-discharge cycle characteristics by including a lithium-excess positive electrode active material and carbon fibers in the positive electrode.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent No. 6595506 Summary of the Invention
[0006] Patent Document 1 discloses a positive electrode active material containing Ni, Mn, and Co. However, in the lithium transition metal composite oxide contained in the positive electrode active material, the design considers increasing the Ni content to obtain high battery capacity and decreasing the Co content to reduce manufacturing costs. However, in lithium transition metal composite oxides containing a large amount of Ni that essentially does not contain Co, cracks occur in the positive electrode active material due to charge and discharge cycles, resulting in higher battery resistance and sometimes worse charge-discharge cycle characteristics. Patent Document 1's technology does not consider the balance between battery resistance and charge-discharge cycle characteristics, leaving room for improvement.
[0007] As one aspect of this disclosure, the positive electrode for a non-aqueous electrolyte secondary battery comprises a positive current collector and a positive electrode flux layer formed on the surface of the positive current collector. The positive electrode flux layer contains at least: a positive electrode active material comprising a lithium transition metal composite oxide, and carbon fibers, wherein the lithium transition metal composite oxide has a layered rock salt structure, substantially does not contain Co, and contains at least Ni, Al, and Ca.
[0008] As one aspect of this disclosure, a non-aqueous electrolyte secondary battery includes the aforementioned positive electrode, negative electrode, and non-aqueous electrolyte for a non-aqueous electrolyte secondary battery.
[0009] According to one aspect of the present disclosure, a positive electrode active material for a non-aqueous electrolyte secondary battery can reduce the resistance of the secondary battery and suppress the decrease in battery capacity during charging and discharging. Attached Figure Description
[0010] Figure 1This is a longitudinal cross-sectional view of a non-aqueous electrolyte secondary battery as an example of an implementation. Detailed Implementation
[0011] In secondary batteries, lithium transition metal composite oxides (LTMOs), which serve as the positive electrode active material, sometimes develop cracks due to charging and discharging. If cracks form in the LTMO, conductive pathways cannot be formed within it, creating areas unfavorable for charging and discharging, sometimes resulting in a decrease in battery capacity. Furthermore, cracks reduce the contact area with the conductive agent, sometimes increasing battery resistance. In such cases, if the LTMO contains Co, the high electronic conductivity of Co can mitigate the impact of increased resistance caused by cracks. However, when increasing the Ni content to achieve high battery capacity and decreasing the Co content to reduce manufacturing costs, it is necessary to suppress the decrease in charge-discharge cycle characteristics and the increase in battery resistance. The inventors have conducted in-depth research on these issues and discovered that by adding Ca to a positive electrode active material containing a large amount of Ni (without Co) and including carbon fibers in the positive electrode composite layer, a synergistic effect can be utilized to specifically suppress the decrease in charge-discharge cycle characteristics and the increase in battery resistance. In particular, in cathodes containing lithium-excess positive electrode active materials, unstable oxygen tends to exist near the surface, which can easily reduce charge-discharge cycle characteristics. Therefore, the effects of this disclosure are significant.
[0012] Hereinafter, an example of an embodiment of the non-aqueous electrolyte secondary battery of the present disclosure will be described in detail. The example described below is a cylindrical battery in which a wound electrode body is housed in a cylindrical battery casing. However, the electrode body is not limited to a wound type; it can also be a stacked type, in which multiple positive electrodes and multiple negative electrodes are alternately stacked one sheet at a time, separated by separators. Furthermore, the battery casing is not limited to a cylindrical shape; for example, it can be square, coin-shaped, or a battery casing made of a laminate containing a metal layer and a resin layer.
[0013] Figure 1 This is a longitudinal cross-sectional view of a non-aqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 As exemplified, the non-aqueous electrolyte secondary battery 10 includes an electrode body 14, a non-aqueous electrolyte, and a battery casing 15 for housing the electrode body 14 and the non-aqueous electrolyte. The electrode body 14 has a wound structure formed by winding a positive electrode 11 and a negative electrode 12 with a separator 13 in between. The battery casing 15 consists of a bottomed cylindrical casing 16 and a sealing body 17 that blocks the opening of the casing 16.
[0014] The electrode body 14 comprises an elongated positive electrode 11, an elongated negative electrode 12, two elongated spacers 13, a positive electrode tab 20 bonded to the positive electrode 11, and a negative electrode tab 21 bonded to the negative electrode 12. The negative electrode 12 is formed to be slightly larger than the positive electrode 11 to prevent lithium deposition. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in both the length and width directions (width direction). The two spacers 13 are formed to be at least slightly larger than the positive electrode 11, for example, in a manner that clamps the positive electrode 11.
[0015] The non-aqueous electrolyte secondary battery 10 has insulating plates 18 and 19 respectively disposed above and below the electrode body 14. Figure 1 In the example shown, the positive electrode tab 20 installed on the positive electrode 11 extends towards the sealing body 17 through the through hole in the insulating plate 18, and the negative electrode tab 21 installed on the negative electrode 12 extends towards the bottom of the outer casing 16 through the outer side of the insulating plate 19. The positive electrode tab 20 is connected to the lower surface of the bottom plate 23 of the sealing body 17 by welding or the like, and the cover 27 of the sealing body 17, which is electrically connected to the bottom plate 23, becomes the positive terminal. The negative electrode tab 21 is connected to the inner bottom surface of the outer casing 16 by welding or the like, and the outer casing 16 becomes the negative terminal.
[0016] The outer casing 16 is, for example, a bottomed cylindrical metal container. A gasket 28 is provided between the outer casing 16 and the sealing body 17, sealing the internal space of the battery casing 15. The outer casing 16 has, for example, a groove 22 formed from the externally pressurized side to support the sealing body 17. The groove 22 is preferably formed in a ring shape along the circumference of the outer casing 16, and its upper surface supports the sealing body 17.
[0017] The sealing body 17 has a structure in which a base plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cover 27 are stacked sequentially from the electrode body 14 side. Each component constituting the sealing body 17 has, for example, a circular or annular shape, and all components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective central portions, and the insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat dissipation, the lower valve body 24 deforms and breaks by pushing the upper valve body 26 towards the cover 27 side, thus blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and gas is discharged from the opening of the cover 27.
[0018] The following details the positive electrode active material contained in the positive electrode 11, negative electrode 12, separator 13, and non-aqueous electrolyte, particularly the positive electrode compound layer 31 constituting the positive electrode 11, which constitute the non-aqueous electrolyte secondary battery 10.
[0019] [positive electrode]
[0020] The positive electrode 11 includes a positive current collector 30 and a positive electrode flux layer 31 formed on the surface of the positive current collector 30. The positive electrode flux layer 31 can be formed on both surfaces of the positive current collector 30. As for the material of the positive current collector 30, for example, foils of metals such as stainless steel, aluminum, aluminum alloy, and titanium, and thin films of such metals disposed on the surface can be used.
[0021] The positive electrode additive layer 31 contains at least a positive electrode active material and carbon fibers. The thickness of the positive electrode additive layer 31 is, for example, 10 μm to 150 μm on one side of the positive electrode current collector 30. The positive electrode 11 can be manufactured, for example, by coating the surface of the positive electrode current collector 30 with a positive electrode slurry containing a positive electrode active material, carbon fibers, etc., drying the coating, and then compressing it to form the positive electrode additive layer 31 on both sides of the positive electrode current collector 30.
[0022] The positive electrode active material comprises a lithium transition metal composite oxide. This lithium transition metal composite oxide has a layered rock salt structure. Examples of layered rock salt structures belonging to space group R-3m and space group C2 / m are examples of such structures. From the viewpoints of high capacity and stable crystal structure, the lithium transition metal composite oxide preferably has a layered rock salt structure belonging to space group R-3m.
[0023] The preferred crystallite diameter s of lithium transition metal composite oxides More Special Selection Furthermore, within this range, a smaller crystallite diameter *s* results in improved charge-discharge cycle characteristics and lower battery resistance, making it a preferred option. The crystallite diameter *s* of lithium transition metal composite oxides is smaller than... In such cases, reduced crystallinity can sometimes lead to a decrease in battery capacity. Furthermore, the crystallite diameter s of lithium transition metal composite oxides exceeds [a certain value]. In certain conditions, the diffusion of Li deteriorates, and the power characteristics of the battery sometimes decrease.
[0024] The crystallite diameter *s* of the lithium transition metal composite oxide is calculated from the half-width *n* of the diffraction peaks on the (003) plane of the X-ray diffraction pattern using the Scherrer equation. The Scherrer equation is expressed as follows.
[0025] s=Kλ / Bcosθ
[0026] In the above formula, s is the crystallite diameter, λ is the wavelength of the X-ray, B is the half-width of the diffraction peak of the (003) plane, θ is the diffraction angle (rad), and K is the Scherer constant. In this embodiment, K is set to 0.9.
[0027] The X-ray diffraction pattern was obtained using a powder X-ray diffraction apparatus (manufactured by Rigaku Co., Ltd., trade name "RINT-TTR", X-ray source Cu-Kα) according to the powder X-ray diffraction method based on the following conditions.
[0028] Measurement range: 15-120°
[0029] Scanning speed: 4° / minute
[0030] Resolution range: 30-120°
[0031] Background: B-spline
[0032] Curve functions: Segmentation-type fitting Voigt function
[0033] Bounding condition: Li(3a) + Ni(3a) = 1
[0034] Ni(3a) + Ni(3b) = α (α is the proportion of Ni contained in each)
[0035] ICSD No.: 98-009-4814
[0036] Lithium transition metal composite oxides can be, for example, secondary particles formed by the aggregation of multiple primary particles. The particle size of the primary particles constituting the secondary particles is, for example, 0.02 μm to 2 μm. The particle size of the primary particles is determined by the diameter of the circumcircle in the particle image observed by a scanning electron microscope (SEM).
[0037] Secondary particles of lithium transition metal composite oxides can have a median particle size (D50) on a volume basis, for example, 2 μm to 30 μm, preferably 2 μm to 20 μm, and more preferably 6 μm to 15 μm. D50 refers to the particle size at which the cumulative frequency in the volume-based particle size distribution reaches 50% from the smallest particle size; it is also known as the median diameter. The particle size distribution of secondary particles of lithium transition metal composite oxides can be measured using a laser diffraction-based particle size distribution measuring device (e.g., MicrotracBEL Corp., MT3000II) with water as the dispersion medium.
[0038] Lithium transition metal oxides are substantially free of Co and contain at least Ni, Al, and Ca. Here, "substantially free of Co" means that the lithium transition metal oxide contains only less than 0.01 mol% of Co relative to the total amount of metals other than Li. Co is expensive; therefore, by substantially eliminating Co, manufacturing costs can be reduced.
[0039] The Ni content in the lithium transition metal composite oxide can be 80 mol% or more relative to the total amount of metal elements other than Li. This can improve the battery capacity. Preferably, the Ni content in the lithium transition metal composite oxide is 85 mol% or more, more preferably 90 mol% or more relative to the total amount of metal elements other than Li. Furthermore, the Ni content in the lithium transition metal composite oxide is preferably 96 mol% or less relative to the total amount of metal elements other than Li.
[0040] The Al content in lithium transition metal composite oxides is preferably 1 mol% to 10 mol% relative to the total amount of metal elements other than Li, more preferably 3 mol% to 8 mol%. Since Al does not readily undergo oxidation number changes during charging and discharging, it is believed that its inclusion in the transition metal layer within the layered rock salt structure stabilizes the transition metal layer structure. On the other hand, when the Al content is 10 mol% or more, Al impurities are generated, and the battery capacity may sometimes decrease.
[0041] The Ca content in lithium transition metal composite oxides can be less than 0.5 mol% relative to the total amount of metal elements other than Li. If the Ca content exceeds 0.5 mol%, the battery resistance may sometimes increase due to the Ca compounds. By containing Ca, lithium transition metal composite oxides can further improve particle strength through the synergistic effect with carbon fibers described later, thereby improving charge-discharge cycle characteristics and reducing battery resistance. Furthermore, the Ca content in lithium transition metal composite oxides is preferably 0.1 mol% or more relative to the total amount of metal elements other than Li. When the Ca content is less than 0.1 mol%, the effect of improving particle strength may not be sufficiently obtained. By improving particle strength, the formation of cracks in lithium transition metal composite oxides during charge and discharge can be suppressed.
[0042] Lithium transition metal composite oxides may also contain Mn. This improves the thermal stability of the lithium transition metal composite oxides. The Mn content in the lithium transition metal composite oxide, relative to the total amount of metal elements other than Li, is preferably 0 mol% to 15 mol%, more preferably 1 mol% to 10 mol% or less.
[0043] Lithium transition metal composite oxides may also contain Nb. This reduces resistance and improves initial coulombic efficiency during charge and discharge. The Nb content in the lithium transition metal composite oxide is preferably 0 mol% to 0.5 mol% relative to the total amount of metal elements other than Li, more preferably 0 mol% to 0.3 mol%.
[0044] Lithium transition metal composite oxides can be of the general formula Li a Ni x Al y Mn z Mu Ca v Nb w O 2-b (where 0.9≤a≤1.1, 0.80≤x≤0.96, 0.01≤y≤0.10, 0≤z≤0.15, 0≤u≤0.10, 0<v≤0.005, 0≤w≤0.005, 0≤b≤0.05, x+y+z+v+w=1, and M contains at least one element selected from Fe, Ti, Si, Zr, Mo, and Zn) represents the composite oxide. The molar fraction of metal elements contained in the overall particles of the lithium transition metal composite oxide was determined by inductively coupled plasma (ICP) emission spectroscopy. It should be noted that Ca and Nb can be dissolved in the lithium transition metal composite oxide, or they can exist on the surface of the primary particles of the lithium transition metal composite oxide. For example, Ca and Nb can be partially dissolved in the lithium transition metal composite oxide and partially exist on the surface of the primary particles of the lithium transition metal composite oxide. From the viewpoint of improving the particle strength of lithium transition metal composite oxides, it is preferable that at least a portion of Ca exists on the surface of the primary particles of lithium transition metal composite oxides.
[0045] The content of lithium transition metal composite oxide in the positive electrode active material is preferably 90% by mass or more, more preferably 99% by mass or more, relative to the total mass of the positive electrode active material, for example, in terms of improving battery capacity and effectively suppressing the reduction of charge-discharge cycle characteristics.
[0046] In addition to the lithium transition metal composite oxide of this embodiment, the positive electrode active material may also include other lithium transition metal composite oxides. Examples of other lithium transition metal composite oxides include lithium transition metal composite oxides with a Ni content of 0 mol% or more and less than 80 mol%.
[0047] Next, an example of a method for manufacturing lithium transition metal composite oxides will be described.
[0048] The method for manufacturing the positive electrode active material may include, for example, the following steps: a first step of obtaining a composite oxide containing Ni, Al and any metal element; a second step of mixing the composite oxide obtained in the first step with a Li compound to obtain a mixture; and a third step of calcining the mixture.
[0049] In the first step, for example, by stirring a solution containing Ni, Al, and any metal element (Mn, Fe, etc.) while adding an alkaline solution such as sodium hydroxide dropwise, the pH is adjusted to the alkaline side (e.g., 8.5–12.5), causing a composite hydroxide containing Ni, Al, and any metal element to precipitate (co-precipitate). This composite hydroxide is then calcined to obtain a composite oxide containing Ni, Al, and any metal element. The calcination temperature is not particularly limited, and can be in the range of 300°C to 600°C.
[0050] In the second step, the composite oxide, Li compound, and Ca compound obtained in the first step are mixed to obtain a mixture. Examples of Li compounds include Li₂CO₃, LiOH, Li₂O₂, Li₂O, LiNO₃, LiNO₂, Li₂SO₄, LiOH·H₂O, LiH, and LiF. Examples of Ca compounds include Ca(OH)₂, CaO, CaCO₃, CaSO₄, and Ca(NO₃)₂. The particle size of the Ca compound is preferably 0.1 μm or more and 20 μm or less. If the Ca compound contains moisture, it can be dehydrated by drying or other methods before use to suppress moisture generation during firing. Additionally, an Nb compound can be further mixed in. Examples of Nb compounds include Nb₂O₅, Nb₂O₅·nH₂O, LiNbO₃, and NbCl₅. The particle size of the Nb compound is preferably 0.1 μm or more and 20 μm or less. If the Nb compound contains moisture, it can be dehydrated by drying or other methods before use to suppress moisture generation during firing. The mixing ratio of the aforementioned composite oxide with the Li compound, Ca compound, and Nb compound can be suitably determined so that the elements in the final Li transition metal oxide are in the desired proportions. Preferably, the molar ratio of the metal element other than Li to Li is in the range of 1:0.9 to 1:1.1. The Ca content in the total amount of metal elements other than Li is, for example, 0.5 mol% or less. Furthermore, when Nb is added, the Nb content in the total amount of metal elements other than Li is, for example, 0.5 mol% or less, preferably 0.3 mol% or less. In the second step, when mixing the composite oxide obtained in the first step with the Li compound, other metal raw materials may be added as needed. These other metal raw materials are oxides containing metal elements other than those constituting the composite oxide obtained in the first step.
[0051] In the third step, the mixture obtained in the second step is calcined in an oxygen atmosphere to obtain the lithium transition metal composite oxide of this embodiment. In the third step, the heating rate can be between 450°C and 680°C, ranging from 1.0°C / min to 5.5°C / min, and the maximum temperature can be between 700°C and 850°C. The heating rate between 450°C and 680°C can be between 0.1°C / min and 5.5°C / min, or between 0.2°C / min and 5.5°C / min. The heating rate from 680°C to the maximum temperature can be set to, for example, 0.1°C / min to 3.5°C / min. Furthermore, the holding time at the maximum temperature can be between 1 hour and 10 hours. Additionally, the third step can be a multi-stage calcination process; the first and second heating rates only need to be within the above-defined ranges, and multiple rates can be set in each temperature zone.
[0052] In the manufacturing method of this embodiment, to improve battery capacity and safety, the lithium transition metal composite oxide powder obtained in the third step can be washed with water. This washing can be performed using known methods and conditions, as long as it is performed within the range where lithium is dissolved from the lithium transition metal composite oxide without deterioration of battery characteristics. Furthermore, a W compound can be mixed before and after the washing. Examples of this W compound include tungsten oxide (WO3), lithium tungstate (Li2WO4, Li4WO5, Li6W2O9), etc. When mixing is performed after washing, it can be done after drying, or it can be done solely through solid-liquid separation without drying; any method can be used.
[0053] The carbon fibers contained in the positive electrode binder layer 31 function as a conductive agent. The content of carbon fibers in the positive electrode binder layer can be 0.01 to 1 part by mass relative to 100 parts by mass of the positive electrode active material. It is believed that by including carbon fibers in the positive electrode binder layer in the above-mentioned specified amount, the conductive path of the positive electrode binder layer can be ensured, which is beneficial to suppressing the capacity reduction accompanied by charge-discharge cycles. When the carbon fiber content is less than 0.01 parts by mass, the conductive path of the positive electrode binder layer cannot be sufficiently ensured. In addition, when the carbon fiber content exceeds 1 part by mass, it is easy to hinder the movement of non-aqueous solvents and electrolytes in the positive electrode binder layer. In either case, it is easy to cause the capacity reduction accompanied by charge-discharge cycles. Furthermore, if it is within this range, according to the synergistic effect with Ca contained in the positive electrode active material, the particle strength can be further improved, the charge-discharge cycle characteristics can be improved, and the battery resistance can be reduced.
[0054] As for carbon fibers, well-known materials used as conductive agents in batteries can be cited, such as carbon nanotubes (CNTs), carbon nanofibers (CNFs), vapor-deposited carbon fibers (VGCFs), electric field-spun carbon fibers, polyacrylonitrile (PAN) based carbon fibers, and pitch-based carbon fibers.
[0055] For example, from the viewpoint of improving the conductivity of the carbon fiber itself, and from the viewpoint that adding a small amount of carbon fiber with improved conductivity can ensure the conductive path of the positive electrode binder layer, the outermost diameter of the carbon fiber is preferably 1 nm to 20 nm, more preferably 1.5 nm to 10 nm. The outermost diameter of the carbon fiber is the average of the outer diameters of any 50 carbon fibers measured by field emission scanning microscopy (FE-SEM) or transmission electron microscopy (TEM).
[0056] For example, to ensure the conductive pathways between the active materials in the positive electrode layer, the fiber length of the carbon fiber is preferably 0.1 μm to 20 μm, more preferably 1 μm to 10 μm, and particularly preferably 1 μm to 5 μm. The fiber length of the carbon fiber is the average length of any 50 carbon fibers measured by a field emission scanning microscope (FE-SEM).
[0057] In the carbon fibers described above, carbon nanotubes are preferably incorporated, for example, to further suppress capacity reduction during charge-discharge cycling. Examples of carbon nanotubes include single-layer carbon nanotubes, two-layer carbon nanotubes, and multi-layer carbon nanotubes. A single-layer carbon nanotube (SWCNT) is a carbon nanostructure consisting of one layer of graphene sheets forming a cylindrical shape; a two-layer carbon nanotube is a carbon nanostructure consisting of two concentrically stacked graphene sheets forming a cylindrical shape; and a multi-layer carbon nanotube is a carbon nanostructure consisting of three or more concentrically stacked graphene sheets forming a cylindrical shape. It should be noted that a graphene sheet refers to a layer in which the carbon atoms of the sp2 hybrid orbitals constituting the graphite crystal are located at the vertices of a hexagonal shape. The shape of the carbon nanotubes is not limited. Examples of the shapes include needle-like, cylindrical, fishbone-like (fishbone or cup stacked), playing card-like (sheet), and coil-like forms.
[0058] The carbon nanotubes contained in the positive electrode binder layer are preferably monolayer carbon nanotubes. Typically, monolayer carbon nanotubes form conductive pathways in the positive electrode binder layer in smaller quantities than multilayer carbon nanotubes. Therefore, it is believed that including a small amount of monolayer carbon nanotubes in the positive electrode binder layer facilitates the movement of non-aqueous solvents and electrolytes within the binder layer. It should be noted that the positive electrode binder layer may contain not only monolayer carbon nanotubes, but also two-layer or multilayer carbon nanotubes.
[0059] The positive electrode additive layer may also contain particulate conductive agents, and the content of the particulate conductive agents in the positive electrode additive layer may be 3 parts by mass or less relative to 100 parts by mass of the positive electrode active material. By making the particulate conductive agents contained in the positive electrode additive layer to the above-mentioned specified amount, the conductivity between the positive electrode active material particles is improved, and the power characteristics of the battery are sometimes improved. Examples of particulate conductive agents include carbon materials such as carbon black, acetylene black, Ketjen black, and graphite. They can be used alone or in combination of two or more. When using particulate conductive agents, the primary particle size is preferably 5 nm or more and 100 nm or less.
[0060] The positive electrode binder layer 31 may also include a binder. Examples of binders include fluorinated polymers and rubber-based polymers. Examples of fluorinated polymers include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), or their modifiers. Examples of rubber-based polymers include ethylene-propylene-isoprene copolymers and ethylene-propylene-butadiene copolymers. One type may be used alone, or two or more may be used in combination.
[0061] [negative electrode]
[0062] The negative electrode 12 includes a negative electrode current collector 40 and negative electrode binder layers 41 formed on both sides of the negative electrode current collector 40. The negative electrode current collector 40 can be a foil of a metal that is stable within the potential range of the negative electrode 12, such as copper or a copper alloy, or a thin film of the metal disposed on its surface. The negative electrode binder layer 41 can contain a negative electrode active material and a binder. For example, the thickness of the negative electrode binder layer 41 on one side of the negative electrode current collector 40 is 10 μm to 150 μm. The negative electrode 12 can be manufactured, for example, by coating a negative electrode slurry containing a negative electrode active material and a binder onto the surface of the negative electrode current collector 40, drying the coating, calendering it, and forming the negative electrode binder layer 41 on both sides of the negative electrode current collector 40.
[0063] As the negative electrode active material contained in the negative electrode additive layer 41, there are no particular limitations as long as it can reversibly absorb, store, and release lithium ions; carbon materials such as graphite are commonly used. Graphite can be natural graphite such as flake graphite, block graphite, and amorphous graphite, or artificial graphite such as block graphite and graphitized mesophase carbon microspheres. Additionally, as the negative electrode active material, metals alloyed with Li such as Si and Sn, metal compounds containing Si and Sn, and lithium-titanium composite oxides can be used. Furthermore, materials with a carbon coating can also be used. For example, SiO₂ can be used. x (0.5≤x≤1.6) represents Si-containing compounds or Li 2y SiO (2+y) The fine particles of Si shown in (0<y<2) are dispersed in the lithium silicate phase and are used in combination with Si-containing compounds and graphite.
[0064] Similar to the case of the positive electrode 11, the binder contained in the negative electrode binder layer 41 can be fluorinated resins such as PTFE and PVdF, PAN, polyimide, acrylic resins, polyolefins, etc., with styrene-butadiene rubber (SBR) being preferred. Furthermore, the negative electrode binder layer 41 may contain CMC or its salts, polyacrylic acid (PAA) or its salts, polyvinyl alcohol (PVA), etc.
[0065] [Separator]
[0066] The separator 13 uses, for example, a porous sheet with ion permeability and insulation properties. Specific examples of porous sheets include microporous films, woven fabrics, and nonwoven fabrics. Suitable materials for the separator include polyolefins such as polyethylene and polypropylene, and cellulose. The separator 13 can be a single-layer structure or a multilayer structure. Furthermore, a resin layer with high heat resistance, such as an aromatic polyamide resin, or a filler layer containing inorganic compounds can be provided on the surface of the separator 13.
[0067] [Non-aqueous electrolytes]
[0068] Non-aqueous electrolytes may include, for example, a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent may be, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixtures of two or more of these solvents. The non-aqueous solvent may contain a halogen substitute formed by replacing at least a portion of the hydrogen atoms of these solvents with halogen atoms such as fluorine. Examples of halogen substitutes include fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, and fluorinated chain carboxylic acid esters such as methyl fluoropropionate (FMP).
[0069] Examples of the aforementioned esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butyl carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylic acid esters such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); and chain carboxylic acid esters such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate (EP).
[0070] Examples of the aforementioned ethers include cyclic ethers such as 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-epoxybutane, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-eudesmol, crown ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, and dibutyl ether. Chain ethers such as dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, etc.
[0071] The preferred electrolyte salt is a lithium salt. Examples of lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), and LiPF6. 6-x (C n F 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10 LiCl, LiBr, LiI, lithium chloroborane, lower aliphatic carboxylic acids, Li₂B₄O₇, Li(B(C₂O₄)F₂) and other borates, LiN(SO₂CF₃)₂, LiN(C₁F₂) 2l+1 SO2)(C m F 2m+1 Imidamine salts such as SO2 (where l and m are integers greater than or equal to 0) are used. These lithium salts can be used alone or in mixtures. From the viewpoint of ionic conductivity and electrochemical stability, LiPF6 is preferred. The concentration of the lithium salt is, for example, 0.8 mol to 1.8 mol per 1 L of non-aqueous solvent. Furthermore, vinylene carbonate and propanesulfonate lactone additives can be further added.
[0072] <Example>
[0073] The present disclosure will be further described below with reference to embodiments and comparative examples, but the present disclosure is not limited to the following embodiments.
[0074] [Preparation of positive electrode active material]
[0075] <Example 1>
[0076] [Ni] obtained by co-precipitation method0.82 Al 0.05 Mn 0.13 The composite hydroxide shown in [(OH)2] was calcined at 500°C for 8 hours to obtain the composite oxide (Ni). 0.82 Al 0.05 Mn 0.13 (Step 1) The composite oxide was mixed with Ca(OH)₂ and Nb₂O₅ such that the total amount of Ni, Al, and Mn, and the contents of Ca and Nb were 0.25 mol% and 0.22 mol% respectively relative to the total amount of Ni, Al, Mn, Ca, and Nb to Li were further mixed with lithium hydroxide (LiOH) in a molar ratio of 1:1.03 (Step 2). The mixture was heated from room temperature to 650°C in an oxygen stream at a heating rate of 2.0°C / min, and then calcined from 650°C to 750°C at a heating rate of 0.5°C / min to obtain a calcined product. The calcined product was washed with water to remove impurities to obtain the positive electrode active material of Example 1 (Step 3).
[0077] The composition of the positive electrode active material in Example 1 was analyzed using an ICP emission spectrometer (Thermo Fisher Scientific, trade name "iCAP6300"), and the result was LiNi. 0.816 Al 0.05 Mn 0.129 Ca 0.0025 Nb 0.002 2O2. Observations based on energy-dispersive X-ray spectroscopy (TEM-EDX) confirmed the presence of Ca on the surface of the lithium transition metal composite oxide. Furthermore, the crystallite diameter s of the positive electrode active material in Example 1, calculated from the X-ray diffraction pattern, was...
[0078] In addition, the particle strength of the positive electrode active material of Example 1 was determined using a micro compression testing machine (manufactured by Shimadzu Corporation, model name "MCT-211"). Under a compressive load of 90 mN and a loading speed of 2.66 mN / s, the breaking load when the secondary particles of the positive electrode active material of Example 1 were destroyed was measured. The average value of the breaking loads for five positive electrode active materials was taken as the particle strength.
[0079] [The production of the positive electrode]
[0080] 100 parts by weight of the positive electrode active material from Example 1, 0.1 parts by weight of carbon nanotubes (outermost diameter (φ) of 1.5 nm, fiber length (L) of 5 μm) as a conductive agent, 1 part by weight of acetylene black (AB), and 2 parts by weight of polyvinylidene fluoride as a binder were mixed. This mixture was further mixed with N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. Then, the slurry was coated onto a 15 μm thick positive electrode current collector formed of aluminum foil. After the coating dried, it was calendered using calendering rollers and cut into specified electrode sizes to obtain a positive electrode with positive electrode binder layers formed on both sides of the positive electrode current collector. It should be noted that a portion of the positive electrode has an exposed portion on the surface of the positive electrode current collector.
[0081] [Making the negative electrode]
[0082] Natural graphite was used as the negative electrode active material. A negative electrode slurry was prepared by mixing the negative electrode active material with sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR) in an aqueous solution at a solid component mass ratio of 100:1:1. This negative electrode slurry was coated onto both sides of a negative electrode current collector formed from copper foil. After the coating dried, it was calendered using calendering rollers and cut into specified electrode sizes, resulting in a negative electrode with a negative electrode mixture layer formed on both sides of the negative electrode current collector. It should be noted that a portion of the negative electrode has an exposed portion on the surface of the negative electrode current collector.
[0083] [Preparation of non-aqueous electrolytes]
[0084] Ethyl carbonate (EC), methyl ethyl carbonate (MEC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4. Lithium hexafluoride phosphate (LiPF6) was dissolved in this mixed solvent to a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.
[0085] [Fabrication of the Experimental Battery Cell]
[0086] Aluminum leads are installed on the exposed portion of the positive electrode, and nickel leads are installed on the exposed portion of the negative electrode. The positive and negative electrodes are then wound in a spiral pattern with a polyolefin separator in between to create a wound electrode body. This electrode body is then housed in a casing, injected with the non-aqueous electrolyte, and the opening of the casing is sealed to obtain the test battery cell.
[0087] [Evaluation of Capacity Maintenance Rate]
[0088] For the above-mentioned test battery cells, the following cycle test was conducted. The discharge capacity of the first cycle and the discharge capacity of the 100th cycle were determined, and the capacity retention rate was calculated according to the following formula.
[0089] Capacity retention (%) = (Discharge capacity in the 100th cycle ÷ Discharge capacity in the 1st cycle) × 100
[0090] <Cyclic Test>
[0091] For the test battery cell, it was charged at a constant current of 0.3 It at a temperature of 45°C until the battery cell voltage reached 4.2V, and then charged at a constant voltage of 4.2V until the current value reached 1 / 50 It. Afterwards, it was discharged at a constant current of 0.5 It until the battery cell voltage reached 2.5V. This charge-discharge cycle was repeated 100 times.
[0092] [Evaluation of reactive resistance]
[0093] At 25°C, the battery cell was charged with a constant current of 0.3 It until the cell voltage reached 4.2V. Then, it was charged with a constant voltage of 4.2V until the current reached 1 / 50 It. Next, it was discharged with a constant current of 0.5 It until the cell voltage reached 2.5V. Then, at 25°C again, it was charged with a constant current of 0.3 It until the cell voltage reached 4.2V. Then, it was charged with a constant voltage of 4.2V until the current reached 1 / 50 It. Then, for the test cell, the AC impedance from 20kHz to 0.01Hz was measured using an AC impedance meter. A Nyquist plot was plotted from the measured data, and the reactive resistance was determined from the size of the arc between 10kHz and 0.1Hz.
[0094] <Comparative Example 1>
[0095] In the second step, no Ca(OH)2 is added to prepare the positive electrode active material. No AB is added in the preparation of the positive electrode. Otherwise, the positive electrode active material is prepared in the same manner as in Example 1, and the test battery cell is evaluated.
[0096] <Example 2>
[0097] In the first process, [Ni] is used. 0.88 Al 0.051 Mn 0.069 The composite hydroxide shown in [(OH)2] yields a composite oxide (Ni 0.88 Al 0.051 Mn 0.069In the second step, the amount of Ca(OH)2 added was changed so that the Ca content was 0.10 mol% relative to the total amount of Ni, Al, and Mn in the above-mentioned composite oxide. In the third step, the maximum temperature was set to 730°C to produce the positive electrode active material. In the production of the positive electrode, CNTs with an outermost diameter (φ) of 8 nm and a fiber length (L) of 2 μm were used. The amount of CNTs and AB added relative to 100 parts by mass of the positive electrode active material was changed to 1 part by mass and 1.5 parts by mass, respectively. Otherwise, the experimental battery cells were evaluated in the same manner as in Example 1. The composition of the obtained positive electrode active material was determined by ICP emission spectroscopy analysis to be LiNi. 0.877 Al 0.051 Mn 0.069 Ca 0.001 Nb 0.0022 O2. Observations based on energy-dispersive X-ray spectroscopy (TEM-EDX) confirmed the presence of Ca on the surface of the lithium transition metal complex oxide.
[0098] <Comparative Example 2>
[0099] In the second step, no Ca(OH)2 is added to prepare the positive electrode active material. No AB is added in the preparation of the positive electrode. Otherwise, the positive electrode active material is obtained in the same way as in Example 2.
[0100] <Example 3>
[0101] In the first process, [Ni] is used. 0.91 Al 0.051 Mn 0.039 The composite hydroxide shown in [(OH)2] yields a composite oxide (Ni 0.91 Al 0.051 Mn 0.039 In the second step, the amount of Ca(OH)2 added was changed so that the Ca content was 0.50 mol% relative to the total amount of Ni, Al, and Mn in the above-mentioned composite oxide. In the third step, the maximum temperature was set to 725°C to produce the positive electrode active material. No AB was added during the production of the positive electrode. Otherwise, the experimental battery cells were evaluated in the same manner as in Example 1. The composition of the obtained positive electrode active material, based on ICP emission spectroscopy analysis, was LiNi. 0.903 Al 0.051 Mn 0.039 Ca 0.005 Nb 0.0022 O2. Observations based on energy-dispersive X-ray spectroscopy (TEM-EDX) confirmed the presence of Ca on the surface of the lithium transition metal complex oxide.
[0102] <Example 4>
[0103] In the third process, the maximum temperature is set to 715°C. Otherwise, the evaluation of the test battery cells is carried out in the same manner as in Example 3.
[0104] <Example 5>
[0105] In the third process, the maximum temperature is set to 705°C. Otherwise, the evaluation of the test battery cells is carried out in the same manner as in Example 3.
[0106] <Example 6>
[0107] In the second step, the amount of Ca(OH)2 added was changed so that the Ca content was 0.10 mol% relative to the total amount of Ni, Al and Mn in the above-mentioned composite oxide. In the third step, the maximum temperature was set to 715°C to produce the positive electrode active material. In the production of the positive electrode, CNTs with an outermost diameter (φ) of 8 nm and a fiber length (L) of 2 μm were used. The amount of CNTs and AB added relative to 100 parts by mass of the positive electrode active material was changed to 0.5 parts by mass and 0.9 parts by mass, respectively. Otherwise, the evaluation of the test battery cells was carried out in the same manner as in Example 3.
[0108] <Example 7>
[0109] In the second step, the amount of Ca(OH)2 added was changed so that the Ca content was 0.20 mol% relative to the total amount of Ni, Al and Mn in the above-mentioned composite oxide. In the third step, the maximum temperature was set to 715°C to produce the positive electrode active material. In the production of the positive electrode, the amount of AB added relative to 100 parts by mass of the positive electrode active material was changed to 2.5 parts by mass. Otherwise, the evaluation of the test battery cell was carried out in the same manner as in Example 3.
[0110] <Example 8>
[0111] In the second step, the amount of Ca(OH)2 added was changed so that the Ca content was 0.25 mol% relative to the total amount of Ni, Al and Mn in the above-mentioned composite oxide. In the third step, the maximum temperature was set to 715°C to produce the positive electrode active material. In the production of the positive electrode, the amount of AB added relative to 100 parts by mass of the positive electrode active material was changed to 0.75 parts by mass. Otherwise, the evaluation of the test battery cell was carried out in the same manner as in Example 3.
[0112] <Comparative Example 3>
[0113] In the second step, no Ca(OH)2 is added. In the third step, the maximum temperature is set to 715°C to produce the positive electrode active material. Otherwise, the evaluation of the test battery cells is carried out in the same manner as in Example 3.
[0114] <Comparative Example 4>
[0115] In the fabrication of the positive electrode, CNTs were not added, and the amount of AB added relative to 100 parts by mass of the positive electrode active material was changed to 0.9 parts by mass. Otherwise, the evaluation of the test battery cells was carried out in the same manner as in Example 3.
[0116] <Example 9>
[0117] In the first process, [Ni] is used. 0.925 Al 0.055 Mn 0.02 The composite hydroxide shown in [(OH)2] yields a composite oxide (Ni 0.925 Al 0.055 Mn 0.02 In the second step, the amount of Ca(OH)2 added was changed so that the Ca content was 0.10 mol% relative to the total amount of Ni, Al, and Mn in the above-mentioned composite oxide. In the third step, the maximum temperature was set to 715°C to prepare the positive electrode active material. In the preparation of the positive electrode, AB was not added, and the amount of CNT added relative to 100 parts by mass of the positive electrode active material was changed to 0.05 parts by mass. Otherwise, the experimental battery cells were evaluated in the same manner as in Example 1. The composition of the obtained positive electrode active material, based on ICP emission spectroscopy analysis, was LiNi. 0.922 Al 0.055 Mn 0.02 Ca 0.001 Nb 0.0022 O2. Observations based on energy-dispersive X-ray spectroscopy (TEM-EDX) confirmed the presence of Ca on the surface of the lithium transition metal complex oxide.
[0118] <Example 10>
[0119] In the second step, the amount of Ca(OH)2 added was changed so that the Ca content was 0.50 mol% relative to the total amount of Ni, Al and Mn in the above-mentioned composite oxide, and the positive electrode active material was prepared. In the preparation of the positive electrode, the amount of CNT and AB added relative to 100 parts by mass of the positive electrode active material was changed to 0.25 parts by mass and 2.5 parts by mass, respectively. Otherwise, the evaluation of the test battery cell was carried out in the same manner as in Example 9.
[0120] <Comparative Example 5>
[0121] In the second step, no Ca(OH)2 is added to prepare the positive electrode active material. In the preparation of the positive electrode, the amount of CNT added relative to 100 parts by mass of the positive electrode active material is changed to 0.1 parts by mass. Otherwise, the evaluation of the test battery cell is carried out in the same manner as in Example 9.
[0122] <Comparative Example 6>
[0123] In the second step, the amount of Ca(OH)2 added was changed so that the Ca content was 0.25 mol% relative to the total amount of Ni, Al and Mn in the above-mentioned composite oxide, and the positive electrode active material was prepared. In the preparation of the positive electrode, CNT was not added, and the amount of AB added relative to 100 parts by mass of the positive electrode active material was changed to 0.75 parts by mass. Otherwise, the evaluation of the test battery cell was carried out in the same manner as in Example 9.
[0124] <Example 11>
[0125] In the first process, [Ni] is used. 0.925 Al 0.06 Mn 0.015 The composite hydroxide shown in [(OH)2] yields a composite oxide (Ni 0.925 Al 0.06 Mn 0.015 In the second step, the amount of Ca(OH)2 added was changed so that the Ca content was 0.50 mol% relative to the total amount of Ni, Al, and Mn in the above-mentioned composite oxide. In the third step, the maximum temperature was set to 715°C to produce the positive electrode active material. In the production of the positive electrode, CNTs with an outermost diameter (φ) of 8 nm and a fiber length (L) of 2 μm were used. The amounts of CNTs and AB added relative to 100 parts by mass of the positive electrode active material were changed to 0.7 parts by mass and 3 parts by mass, respectively. Otherwise, the experimental battery cells were evaluated in the same manner as in Example 1. The composition of the obtained positive electrode active material was determined by ICP emission spectroscopy analysis to be LiNi. 0.918 Al 0.06 Mn 0.015 Ca 0.005 Nb 0.0022 O2. Observations based on energy-dispersive X-ray spectroscopy (TEM-EDX) confirmed the presence of Ca on the surface of the lithium transition metal complex oxide.
[0126] <Comparative Example 7>
[0127] In the second step, no Ca(OH)2 is added to produce the positive electrode active material. Otherwise, the evaluation of the test battery cells is carried out in the same manner as in Example 11.
[0128] <Example 12>
[0129] In the first process, [Ni] is used. 0.93 Al 0.03 Mn 0.04 The composite hydroxide shown in [(OH)2] yields a composite oxide (Ni 0.93 Al 0.03 Mn 0.04In step 3, the maximum temperature was set to 715°C to prepare the positive electrode active material. CNTs with an outermost diameter (φ) of 8 nm and a fiber length (L) of 2 μm were used in the positive electrode preparation. AB was not added, and the amount of CNTs added relative to 100 parts by mass of the positive electrode active material was changed to 0.5 parts by mass. Otherwise, the experimental battery cells were evaluated in the same manner as in Example 1. The composition of the obtained positive electrode active material, based on ICP emission spectroscopy analysis, was LiNi. 0.926 Al 0.03 Mn 0.04 Ca 0.0025 Nb 0.0022 O2. Observations based on energy-dispersive X-ray spectroscopy (TEM-EDX) confirmed the presence of Ca on the surface of the lithium transition metal complex oxide.
[0130] <Comparative Example 8>
[0131] In the second step, no Ca(OH)2 is added to prepare the positive electrode active material. Otherwise, the evaluation of the test battery cells is carried out in the same manner as in Example 12.
[0132] <Example 13>
[0133] In the first process, [Ni] is used. 0.94 Al 0.03 Mn 0.03 The composite hydroxide shown in [(OH)2] yields a composite oxide (Ni 0.94 Al 0.03 Mn 0.03 In the second step, the amount of Ca(OH)2 added was changed so that the Ca content was 0.15 mol% relative to the total amount of Ni, Al, and Mn in the above-mentioned composite oxide. In the third step, the maximum temperature was set to 715°C to prepare the positive electrode active material. In the preparation of the positive electrode, the amount of CNT and AB added relative to 100 parts by mass of the positive electrode active material was changed to 0.4 parts by mass and 1.5 parts by mass, respectively. Otherwise, the experimental battery cell was evaluated in the same manner as in Example 1. The composition of the obtained positive electrode active material was determined by ICP emission spectroscopy analysis to be LiNi. 0.937 Al 0.03 Mn 0.03 Ca 0.0015 Nb 0.0022 O2. Observations based on energy-dispersive X-ray spectroscopy (TEM-EDX) confirmed the presence of Ca on the surface of the lithium transition metal complex oxide.
[0134] <Comparative Example 9>
[0135] In the second step, no Ca(OH)2 is added to prepare the positive electrode active material. Otherwise, the evaluation of the test battery cells is carried out in the same manner as in Example 13.
[0136] <Example 14>
[0137] In the first process, [Ni] is used. 0.94 Al 0.06 The composite hydroxide shown in [(OH)2] yields a composite oxide (Ni 0.94 Al 0.06 In the second step, the amount of Ca(OH)2 added was changed so that the Ca content was 0.10 mol% relative to the total amount of Ni and Al in the above-mentioned composite oxide. In the third step, the maximum temperature was set to 715°C to prepare the positive electrode active material. In the preparation of the positive electrode, the amount of CNT and AB added relative to 100 parts by mass of the positive electrode active material was changed to 0.02 parts by mass and 0.75 parts by mass, respectively. Otherwise, the experimental battery cell was evaluated in the same manner as in Example 1. The composition of the obtained positive electrode active material was determined by ICP emission spectroscopy analysis to be LiNi. 0.937 Al 0.06 Ca 0.001 Nb 0.0022 O2. Observations based on energy-dispersive X-ray spectroscopy (TEM-EDX) confirmed the presence of Ca on the surface of the lithium transition metal complex oxide.
[0138] <Comparative Example 10>
[0139] In the second step, no Ca(OH)2 is added to prepare the positive electrode active material. Otherwise, the evaluation of the test battery cells is carried out in the same manner as in Example 14.
[0140] <Example 15>
[0141] In step 3, pure water was added to the calcined material, stirred, and then filtered / separated to obtain a filter cake-like composition. WO3 powder was then added in a manner where the molar percentage of W relative to the total amount of metal elements other than Li was 0.08 mol%. The mixture was then heat-treated at 250°C in an atmospheric atmosphere for 3 hours to produce the positive electrode active material. Otherwise, the experimental battery cells were evaluated in the same manner as in Example 13. The composition of the obtained positive electrode active material, based on ICP emission spectroscopy analysis, was LiNi. 0.937 Al 0.03 Mn 0.03 Ca 0.0015 Nb 0.0022 W 0.0008 O2. Observations based on energy-dispersive X-ray spectroscopy (TEM-EDX) confirmed the presence of Ca on the surface of the lithium transition metal complex oxide.
[0142] <Comparative Example 11>
[0143] In the second step, no Ca(OH)2 is added to prepare the positive electrode active material. Otherwise, the evaluation of the test battery cells is carried out in the same manner as in Example 15.
[0144] The capacity retention and reactive resistance of the examples and comparative examples are shown in Tables 1-8. Additionally, Tables 1-8 also show the results of ICP emission spectroscopy analysis of the obtained positive electrode active materials. The reactive resistance and capacity retention of the test cell of Example 1 shown in Table 1 are expressed relative to the reactive resistance and capacity retention of the test cell of Comparative Example 1, with 100 as the threshold.
[0145] The reaction resistance and capacity retention of the test battery cells in Example 2 shown in Table 2 are expressed relative to the reaction resistance and capacity retention of the test battery cells in Comparative Example 2, with 100 as the threshold.
[0146] The reaction resistance and capacity retention of the test battery cells of Examples 3-8 and Comparative Example 4 shown in Table 3 are expressed relative to the reaction resistance and capacity retention of the test battery cell of Comparative Example 3, which is set to 100.
[0147] The reaction resistance and capacity retention of the test battery cells in Examples 9, 10 and Comparative Example 6 shown in Table 4 are expressed relative to the reaction resistance and capacity retention of the test battery cell in Comparative Example 5, which is set to 100.
[0148] The reaction resistance and capacity retention of the test cell in Example 11 shown in Table 5 are expressed relative to the reaction resistance and capacity retention of the test cell in Comparative Example 7, which are taken as 100.
[0149] The reaction resistance and capacity retention of the test cell in Example 12 shown in Table 6 are expressed relative to the reaction resistance and capacity retention of the test cell in Comparative Example 8, which are taken as 100.
[0150] The reaction resistance and capacity retention of the test battery cells in Example 13 shown in Table 7 are expressed relative to the reaction resistance and capacity retention of the test battery cells in Comparative Example 9, which are taken as 100.
[0151] The reaction resistance and capacity retention of the test battery cells in Example 14 shown in Table 8 are expressed relative to the reaction resistance and capacity retention of the test battery cells in Comparative Example 10, which are taken as 100.
[0152] The reaction resistance and capacity retention of the test battery cells in Example 15 shown in Table 9 are expressed relative to the reaction resistance and capacity retention of the test battery cells in Comparative Example 11, which are taken as 100.
[0153] [Table 1]
[0154]
[0155] [Table 2]
[0156]
[0157] [Table 3]
[0158]
[0159] [Table 4]
[0160]
[0161] [Table 5]
[0162]
[0163] [Table 6]
[0164]
[0165] [Table 7]
[0166]
[0167] [Table 8]
[0168]
[0169] [Table 9]
[0170]
[0171] In Tables 1-9, compared with the comparative examples, the examples showed higher capacity retention and lower reactive resistance. Furthermore, the particle strength of the examples was also greater than that of the comparative examples. These results indicate that the positive electrode composite layer, comprising a lithium transition metal composite oxide containing a large amount of Ni (which substantially does not contain Co and contains at least Ni, Al, and Ca) and carbon fibers, can reduce the resistance of the secondary battery and suppress the decrease in battery capacity during charge and discharge.
[0172] Explanation of reference numerals in the attached figures
[0173] 10 Non-aqueous electrolyte secondary batteries
[0174] 11 positive electrode
[0175] 12 negative electrode
[0176] 13 partitions
[0177] 14 electrode bodies
[0178] 15 Battery Casing
[0179] 16-shell can
[0180] 17 sealing bodies
[0181] 18, 19 Insulation Boards
[0182] 20 positive electrode tabs
[0183] 21 negative electrode tabs
[0184] 22 Groove section
[0185] 23 base plate
[0186] 24 Lower Valve Body
[0187] 25 Insulating Components
[0188] 26 Upper Valve Body
[0189] 27 covers
[0190] 28 gasket
[0191] 30 Positive Current Collector
[0192] 31 Positive Electrode Mixture Layer
[0193] 40 negative current collector
[0194] 41 Negative Electrode Mixture Layer
Claims
1. A positive electrode for a non-aqueous electrolyte secondary battery, comprising a positive electrode current collector and a positive electrode flux layer formed on the surface of the positive electrode current collector. The positive electrode mixture layer contains at least: a positive electrode active material comprising a lithium transition metal composite oxide, and carbon fibers. The lithium transition metal composite oxide has a layered rock salt structure, substantially contains no Co, and contains at least Ni, Al, and Ca. The Ca content in the lithium transition metal composite oxide is 0.1 mol% or more and 0.5 mol% or less relative to the total amount of metal elements other than Li. The Ni content in the lithium transition metal composite oxide is more than 80 mol% relative to the total amount of metal elements other than Li. The carbon fiber content in the positive electrode mixture layer is 0.01 to 1 part by mass relative to 100 parts by mass of the positive electrode active material.
2. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein, The positive electrode mixture layer also contains particulate conductive agents. The content of the particulate conductive agent in the positive electrode mixture layer is less than 3 parts by mass relative to 100 parts by mass of the positive electrode active material.
3. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein, The lithium transition metal composite oxide also contains Mn.
4. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein, The lithium transition metal composite oxide also contains Nb.
5. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte as described in any one of claims 1 to 4.
Citation Information
Patent Citations
Positive electrode and lithium ion secondary battery
JP2018037380A
Cathode active material for lithium secondary battery
US20120049109A1